Qualitative and Biochemical Assessment of the Impact of Dietary Habits and Body Mass Index on Hemoglobin Levels in Female University Students - Tariq, Hurma; Sohail, Arisha; Qureshi, Shamim Akhter (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To assess the body mass index, dietary habits, signs, symptoms, and biochemical parameters of anemia in female students. METHODOLOGY: The present cross-sectional analytical study was conducted between August and December 2023 at Public Sector University in Karachi, Pakistan. The eligibility criteria were unmarried females aged 18-25 years. Participants with diagnosed hemoglobinopathy or bleeding disorders, nutritional deficiency anemia, previous anemia treatment, and chronic disease were excluded. The sample size was 393 with convenience sampling. Demographic variables, years of education, ethnicity, rural or urban setting, cultural background, monthly family income, Body Mass Index and folic acid/multivitamins supplements were assessed through a validated questionnaire. 5ml of venous blood was collected, and complete blood count and serum iron was measured. WHO criteria were used for anemia diagnosis. Data was analyzed using SPSS 28. T-test and Chi-Square test were used for categorical data. RESULTS: The study found an equal proportion of normal and overweight participants (41%) followed by underweight (18%). Most females skip breakfast, consume vegetables less than three times a week, and consume fruits more than three times. 91% eat fish less than three days a week and consume fast food and soft drinks less frequently. The prevalence of anemia was 46%, followed by mild (13.6%) and moderate (31.8%) anemia, common symptoms experienced included unusual fatigue, weakness, confusion, a loss of focus, and feelings of sadness or depression. CONCLUSION: The B.M.I. and inadequate dietary habits impact the general health and serum iron levels in female students, which can be improved by dietary intervention.